Analisis Manajemen Tingkat Pengelolaan Air Bersih Di Maluku Utara (Studi Kasus Kabupaten Halmahera Selatan) - Prince Charles Heston Runtunuwu; Fahmi Tanjung (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2023)
The purpose of this study was to determine how the influence of the level of clean water demand in the Regional Drinking Water Company (PDAM) of South Halmahera Regency. With a quantitative research approach, in this study, using the population is the customer of the Obi Laiwui District Drinking Water Company (PDAM), which is 3000 household units and the sample used is 44 households. By using multiple linear regression analysis in data analysis, the final results show that the price of water has a significant effect on the demand for clean water. Likewise, total household income and population have a significant effect on the demand for clean water. From the results of this study, it is suggested that PDAM companies carry out routine programs such as surveys regarding satisfaction, problems or obstacles faced by the community in obtaining clean water, such as a program for checking water channels in people's homes and periodic meter changes.